A função autor e a crônica esportiva no Brasil: representações da Copa do Mundo em alguns jornais paulistas e cariocas - Marques, José Carlos [UNESP] (My University, 2010)
From the 1990s, Brazilian newspapers began to refer to the convening of different personalities to comment on the World Cup soccer in their sports pages. This article seeks to examine this phenomenon under the notion that the French philosopher Michel Foucault called the “author function” - one that establishes the existence, circulation and functioning of certain discourses within a specific audience.

A partir da década de 1990, os jornais brasileiros passaram a recorrer à convocação de diferentes personalidades para comentar as Copas do Mundo de futebol em suas páginas esportivas. Este artigo procura analisar esse fenô- meno à luz do conceito que o filósofo francês Michel Foucault chamou de “função autor” – aquela função que se estabelece pela existência, circulação e funcionamento de alguns discursos no seio de determinado público.
The author function and the Sports Chronicles in Brazil: the representations of the World Cup in some
Keywords: Chronic; World Cup Soccer; Brazilian Journalism; Crônica; Copa do Mundo de Futebol; Jornalismo Brasileiro